Concept of Ignorance in Islam; : Semantic Analysis Study of the Words al-jahālah and al-Jāhiliyyah in the Qur'an - Kholid, Husna Hisaba (Institut Agama Islam Persis Bandung, 2024)
The Qur'an as a miracle amazes linguists about the depth of meaning and use of language in it. This aspect of the miracle of language is what makes the Koran remain eternal in its glory until the end of time. However, unfortunately, due to a lack of linguistic understanding and correct interpretation, language terms in the Koran are often misused. The words al-jahālah and al-jahiliyyah are no exception. There are some people who carelessly use the word jāhiliyyah with an incorrect meaning. This research aims to describe the concepts of al-jahālah and al-jāhiliyyah through semantic analysis and interpretation from authoritative Al-Qur'an exegetes. This article is library research that uses documentary techniques to collect data from various verses in the Koran and their interpretations from classical and contemporary tafsir books. The data that has been collected is then analyzed using the content analysis method. The findings in this research show that the word al-jāhalah is used for disgraceful acts whether from the absence or existence of knowledge, while jāhiliyyah is used to refer to teachings or despicable traits before the arrival of Islamic law, both in the psychological, ethical, legal and belief aspects. Through this research, the author hopes that there will be an integrative study of key concepts of language with the Al-Qur'an, such as jāhalah and jāhiliyyah with problematic issues in people's lives in the contemporary era.